2017
DOI: 10.4209/aaqr.2016.05.0174
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Criteria and Organic Air pollutant Emissions from Motorcycles by Using Various Ethanol-Gasoline Blends

Abstract: Studies on the correlation between ethanol-gasoline blends and pollutant emissions of small engine motorcycles are scant. This study examined the effects of ethanol-gasoline blends, containing various ethanol contents, on air pollutant emissions from two four-stroke fuel-injection motorcycles without engine adjustment. Three test blends, separately containing 15 (E15), 20 (E20), and 30 vol% (E30) ethanol in gasoline, were used to power the test motorcycles. Commercial unleaded gasoline was used as the referenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 20 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Hence, the respirator that combines vapor and particle filtration system is proven to be efficient protective equipment for the case of benzene and ethylbenzene exposures. Nevertheless, BTEX exposure can be largely reduced by cutting down the emissions from transportation (source reduction) such as through the utilization of the fuel injection engines powered by ethanol-gasoline mixtures (Yao et al, 2017).…”
Section: Risk Reduction Using Different Type Of Respiratorsmentioning
confidence: 99%
“…Hence, the respirator that combines vapor and particle filtration system is proven to be efficient protective equipment for the case of benzene and ethylbenzene exposures. Nevertheless, BTEX exposure can be largely reduced by cutting down the emissions from transportation (source reduction) such as through the utilization of the fuel injection engines powered by ethanol-gasoline mixtures (Yao et al, 2017).…”
Section: Risk Reduction Using Different Type Of Respiratorsmentioning
confidence: 99%
“…In this study, the quantity of aromatics emitted by gasoline cars was 1.5 times higher than that emitted by E10. Previous studies revealed the reduction of aromatics from ethanol fuels [48][49][50]. Aromatics mainly come from the incomplete combustion of fuels [51], which unquestionably suffer a decrease in quantity as the ethanol content increases.…”
Section: Vehicle Emissionsmentioning
confidence: 99%